University Student Satisfaction A Systematic Literature Review - Mirza Abdi Khairusy; Reni Febriani (Universitas Muhammadiyah Yogyakarta, 2023)
Student satisfaction can indicate the overall university experience, making it a contentious topic in the higher education literature. For this reason, the author conducted systematic literature discussing Student Satisfaction. This review aims to provide the available constructive literature on student satisfaction with a theoretical and empirical background published during the past 5 years, from January 2017- January 2022, to identify student satisfaction definitions and factors influencing student satisfaction. The author searched for articles in three databases (Scopus, Ebsco, and Proquest). The contribution of this research becomes a reference in understanding and determining the factors of student satisfaction in higher education.